Visualization of the Spinal Artery by CT During Embolization for Pulmonary Artery Pseudoaneurysm - Maki, Hiroyuki (Pol J Radiol, 2016)
BACKGROUND: Spinal artery ischemia is a rare but serious complication of embolization for treatment of hemoptysis. When the spinal artery is visualized at angiography, embolization should not be performed. However, it has been reported that spinal artery feeders are not visible on angiography in patients with developing spinal infarction. CASE REPORT: A 70-year-old man with a history of pulmonary aspergillosis had hemoptysis and underwent contrast-enhanced CT, revealing a pulmonary artery pseudoaneurysm (PAP) in the left upper lobe. Systemic angiography from the fifth left intercostal artery showed the PAP at the distal site, but the access route to the PAP was very tortuous and long. Although the spinal branch could not be observed with that angiography, CT during angiography was performed, and it visualized the posterior spinal artery obviously. Thus, the artery distal and proximal to the PAP was then successfully coil-embolized from the pulmonary artery. CONCLUSIONS: CT during angiography may be useful to confirm the presence of the spinal artery for treatment of hemoptysis by embolization.